An empiric path towards fraud detection and protection for NFC-enabled mobile payment system - Pinki Prakash Vishwakarma; Amiya Kumar Tripathy; Srikanth Vemuru (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The synthesis of NFC technology accompanying mobile payment is a state-of-the-art resolution for payment users. In view of rapid development in electronic payment system there is rise in fraudulent activity in banking transactions associated with credit cards and card-not-present transaction. M-Commerce aid the consumers and helps to bestow real-time information in payment system. Due to the familiarization of m-commerce there is cogent increase in the number of fraudulent activities, emerging in billions of dollar loss every year worldwide. To absolute the security breaches, payment transactions could be confined by considering various parameters like user and device authentication, consumer behavior pattern, geolocation and velocity. In this paper we formally assay NFC-enabled mobile payment fraud detection ecosystem using score-based evaluation method. The fraud detection ecosystem will provide a solution based on transaction risk-modeling, scoring transaction, business rule-based, and cross-field referencing. The score-based evaluation method will analyze the transaction and reckon every transaction for fraud risk and take pertinent decision.